FINANCIAL INVESTMENTS AND THEIR CLASSIFICATION - Maralova Mashxura Baxtiyor qizi (Ecomind Press, 2025)
This article examines the system of financial investments that affect the sustainable economic development of our country. In our country, great attention is paid to the further development of the stock market. It is worth noting that the legislative framework has been improved, the conditions for the flow of investments in securities have been analyzed, and conclusions have been drawn.
Keywords: Financial investment, stock, bond, certificate of deposit, promissory note, digital Uzbekistan.